Salivary gland entrance dose in dental radiology - Lopez, Guillermo Alberto; Campos, Paulo Sérgio Flores (Revista de Ciências Médicas e Biológicas, 2014)
Introduction: Soft tissues modify radiation absorption and increase dispersion. It can also influence the density and the contrast of the film, and therefore, the diagnosis accuracy. In order to estimate the relative risk of cancer associated with induction by radiation, it is important to measure radiation doses at organs and tissues. Objective: to evaluate salivary glands entrance dose, with two digital devices in a head and neck phantom. Methodology: Periapical incidences simulations of incisors were conducted and compared with two digital periapical radiological equipment (Kodak® 2200 Intraoral X-ray System) which have similar characteristics. A dry bone skull prototype and an equivalent human tissue material with wax were used. To measure the organ entrance dose: parotid gland and sublingual glands, it was used a solid-state sensor from Radcal®, Accu-Gold® for diagnostic radiology and an ionization chamber from Radcal®, Accu-Gold®, where effective doses were measured in the equipment and in the sensor and then compared. Results: in parotid glands were 0.033 mSv and in sublingual 0.388 mSv. Conclusion: It is important to highlight from the results the importance of using low doses of radiation and the appropriate equipment positioning in order to perform periapical radiological incidences in maxillary and mandibular regions. If the beam it is not corrected positioned, an increase in the radiation dose to organs can occur near to the area of study.